Economic Growth with Tourism and Environmental Change - WEIBIN ZHANG (Yayasan Riset dan Pengembangan Intelektual, 2020)
The main purpose of this study is to examine dynamic interactions between economic growth, environmental change, and tourism. Although tourism is playing an increasingly important role in different economies, there are only a few theoretical models to dynamic economic and environmental issues with endogenous tourism. On the basis of the Solow-Uzawa growth model, the neoclassical growth model with environmental change, and ideas from tourism economics, we develop a three-sector growth model. The industrial and service sectors are perfectly competitive. The environment sector is financially supported by the government. We introduce taxes not only on producers, but also on consumers’ incomes from wage, land, and interest of wealth, consumption of goods and services, and housing. We simulate the motion of the national economy and examine effects of changes in some parameters. The comparative dynamic analysis with regard to the rate of interest, the price elasticity of tourism, the global economic condition, the total productivity of the service sectors, and the propensity to save provides some important insights into the complexity of open economies with endogenous wealth and environment.